Getting Back to Work : Everything You Need to Bounce Back and Get a Job After a Layoff - Rolie, Linda K. (New York McGraw-Hill, 2010)
A comprehensive, action-oriented, job-hunting guide uniquely tailored to people who are suffering the financial and emotional ramifications of having lost their jobs.
Include Index, Appendix and Illustration
Keywords: Career changes -- Career changes--Psychological aspects -- Job hunting